2017
DOI: 10.1016/j.eucr.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted Partial Cystectomy for Treatment of Inflammatory Myofibroblastic Tumor of the Bladder

Abstract: Inflammatory myofibroblastic tumors rarely occur in the urinary bladder. These masses follow an indolent course, but due to their histologic similarities to more malignant types of bladder masses, they must be differentiated with immunohistochemical staining. Once diagnosed, the mainstay of treatment for these masses is surgical resection. Due to advancements in robotic surgery, new surgical techniques can be employed to treat these masses with fewer perioperative complications. We report a case of inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These lesions develop in various organs, such as the lung, retroperitoneum, and pelvis . IMT of the bladder represents less than 1% of all bladder tumors and is therefore one of the most difficult diagnostic dilemmas in genitourinary pathology …”
Section: Discussionmentioning
confidence: 99%
“…These lesions develop in various organs, such as the lung, retroperitoneum, and pelvis . IMT of the bladder represents less than 1% of all bladder tumors and is therefore one of the most difficult diagnostic dilemmas in genitourinary pathology …”
Section: Discussionmentioning
confidence: 99%
“…IMTUB is a rare tumor of indeterminate malignant potential and comprises less than 1% of all bladder tumors. [2] The common manifestations of IMTUB include anemia and gross hematuria, accompanied by pain sometimes during urination. Teoh et al [6] reported that high possibility of IMTUB should be suspected for young patients presenting with gross hematuria and severe anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approach is safe in selected patients and may yield satisfactory oncological and functional results. [13] Recently, Rotenberry et al [2] reported a patient of IMTUB who was treated by robotic-assisted laparoscopic partial cystectomy with good prognosis. Compared with open partial cystectomy, laparoscopic or robot-assisted laparoscopic approach has several advantages, including cosmetic factors, lower risk of postoperative complications and shorter postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What's more, urinary bladder is the most common site of IMTs. Nevertheless, IMTs comprise less than 1% of all bladder neoplasms [4] .…”
Section: Introductionmentioning
confidence: 99%